1991
DOI: 10.1002/zaac.19916010102
|View full text |Cite
|
Sign up to set email alerts
|

Silber(I)‐catena‐Polysilicat Kristallzüchtung und Strukturanalyse

Abstract: Ag2SiO3 wurde unter hydrothermalen Bedingungen aus den binären Komponenten als Pulver und Einkristalle dargestellt. Nach der Röntgenstrukturanalyse (P212121; a = 452,7(1), b = 710,8(1), c = 995,9(1) pm; Z = 4; 1387 Reflexe, 57 Parameter; R = 0,06) handelt es sich um ein catena‐Polysilicat mit einer Zweiereinfachkette. Das UV/VIS‐Spektrum zeigt eine Absorptionskante bei 19 700 cm−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Hence, the anion can be described by the Niggli formula 1 ∞ [B(SO 4 ) 2 (SO 4 ) 2/2 ] 3– }. By eying the corner sharing connection pattern of the supertetrahedra with a B:S ratio of 1:3, unbranched zweier single chains result, comparable to the silicate chains in Ag 2 [SiO 3 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the anion can be described by the Niggli formula 1 ∞ [B(SO 4 ) 2 (SO 4 ) 2/2 ] 3– }. By eying the corner sharing connection pattern of the supertetrahedra with a B:S ratio of 1:3, unbranched zweier single chains result, comparable to the silicate chains in Ag 2 [SiO 3 ] …”
Section: Resultsmentioning
confidence: 99%
“…By eying the corner sharing connection pattern of the supertetrahedra with a B:S ratio of 1:3, unbranched zweier single chains result, comparable to the silicate chains in Ag 2 [SiO 3 ]. [15] Figure 1. Crystal structure of (NH 4 ) 3 (10) pm].…”
Section: Introductionmentioning
confidence: 99%
“…The initial structural parameters of Ag 2 GeO 3 were taken from those of Ag 2 SiO 3 (Jansen et al , 1991). There are six independent sites (i.e., two Ag site, one Ge site, and three O sites) with the Wyckoff position 4 a in the unit cell.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures of these silver germanates, except for Ag 2 GeO 3 , have been successfully determined. Parts of these silver germanates were confirmed to be isostructural with the corresponding silver silicates such as Ag 5 SiO 4 (Linke and Jansen, 1994), Ag 4 SiO 4 (Klein and Jansen, 2008), Ag 6 Si 2 O 7 (Jansen, 1977; Linke and Jansen, 1996a), Ag 10 Si 4 O 13 (Jansen and Keller, 1979),Ag 2 SiO 3 (Jansen et al , 1991), and Ag 2 Si 2 O 5 (Liebau, 1961). The most remarkable common feature of these structures is the relatively short silver-silver distances.…”
Section: Introductionmentioning
confidence: 95%
“…[25] Ag 2 SiO 3 is an important ionic conductor material but has rarely been studied. [26] Recently, we have shown that a family of metal tungstate and molybdate nanowires/nanorods can be easily synthesized by a facile hydrothermal recrystallization technique. [27] Here, we report an efficient route for transforming uniform Ag 6 Mo 10 O 33 nanowires into well-defined hollow Ag 2 SiO 3 / SiO 2 composite nanotubes by a facile sacrificial template approach at room temperature.…”
mentioning
confidence: 99%